The Theoretical Impact of Fiscal Decentralisation on National Income Inequality: Does Quality of Governance Matter? - El Feky, Fakhry; El Nemr, Nadia; Mousa, Sarah (International Journal of Economics and Financial Issues, 2023)
There are long arguments among scholars about whether fiscal decentralisation increases or reduces national income inequality. The optimistic scholars indicate that the efficiency-enhancing effects of fiscal decentralisation to reduce income inequality are more likely to occur in high-economic-level regions since they have inter-jurisdictional competition, accountability, and revenue mobilisation. While the pessimistic view emphasised that fiscal decentralisation might increase income inequality because of low governance quality, which offsets the potential efficiency gains of decentralisation. The finding of this paper is that fiscal decentralisation cannot be optimistic or pessimistic, but after screening the empirical studies, it is based on three trends: the structure and design of fiscal decentralisation, the level of economic development, and the level of governance as a mediator.